A systematic review and meta-analysis on the role of exercise or rest in patients with concussion and mild traumatic brain injury. Issue 11 (25th May 2017) - Lal, Avtar; Kolakowsky-Hayner, Stephanie; Ghajar, Jamshid; Vazquez, Oscar; Balamane, Maya
Abstract : Objective: To conduct a systematic review and meta-analysis evaluating the role of exercise or rest in patients with concussion or mild traumatic brain injury. Design: Systematic review and meta-analysis. Data sources: Medline, PsychInfo, Scopus, Cochrane Controlled Trials Registers and Sport Discus, till March 2016 and hand search of some articles. Study selection: Randomised controlled trials (RCTS) and observational studies (OBS) comparing the effect of exercise or rest in patients with concussion, on different outcomes. Participants: Children and adults with concussion or mild traumatic brain injury. Intervention: Exercise or Rest. Outcomes: Post concussive symptoms (PCCS), balance error scoring system (BESS), immediate post concussion assessment and cognitive testing (ImPACT). Main results: Our search generated 921 studies. Of these, 5 RCTs and 12 OBS met our inclusion criteria. Methodological quality of most of the studies was poor. Meta-analysis of 6 studies involving more than 556 patients showed statistical significant decrease in PCCS with exercise compared to control, Mean Difference (MD) [95% Confidence Interval (CI)], −14.6 [−17.8, −11.3], p<0.001. There was some clinical, but no statistical heterogeneity among the studies (I2=32%). Exercise did not affect BESS, neuropsychological scale and ImPACT score. There was not effect of rest on total symptoms in patients with concussion and number of patients with symptoms. Conclusion: Our systematic review and meta-analysis showed clear benefits of exercise in PCCS. However, the evidence was based on poor quality studies that vary in duration, frequency and intensity of exercise. A good quality RCT needs to be conducted to evaluate a clear effect of exercise and rest in patients with concussion. Competing interests: None.